2016
DOI: 10.17507/jltr.0706.06
|View full text |Cite
|
Sign up to set email alerts
|

English-major Pre-service Teachers’ Language Learning Strategy Use in terms of Enjoyment of English Learning

Abstract: Abstract-Language learning strategies (LLSs) play important roles in learners' language learning. The study investigated the use of LLSs employed by English-major pre-service teachers in Midwest China by enjoyment of English learning. The modified SILL was used to collect the data. ANOVA and Post Hoc Scheffe Test were performed for data analysis. The results demonstrated that a significant variation in their pre-service teachers reported frequency of overall strategy use, all the four categories, and 41 out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Another result of categorization of LLS showed that the last strategy used by learners with low proficiency in this present study is compensation strategies. This is in-line with Zhou and Intaraprasert (2015) compensation strategy also became the last strategy used by learner with low proficiency.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Another result of categorization of LLS showed that the last strategy used by learners with low proficiency in this present study is compensation strategies. This is in-line with Zhou and Intaraprasert (2015) compensation strategy also became the last strategy used by learner with low proficiency.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, the metacognitive strategy is the second strategy used by students with high proficiency in which Rismayana (2017) and Zhou and Intaraprasert (2015) stated as metacognitive strategy to be the most frequently used strategy by learners with high proficiency. However, the learners with low proficiency also used these metacognitive strategies as found in this study and Alfian's (2018) study demonstrating that the metacognitive strategy is strategy used by the learners with both high proficiency and low proficiency levels.…”
Section: Discussionmentioning
confidence: 99%